PENERAPAN MEDIA OPPET (AMPLOP PETUALANG) ASEAN UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS VI SD NEGERI KEDUNGPRIMPEN - Mega Puspita Sari (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
Abstract. Literacy skills are abilities that are not just limited to writing and reading. Literacy skills are the ability to read, write, listen and speak. This ability is really needed by elementary school students to prepare themselves for future competition because of the high demands for skills in the 21st century. So far, social studies learning has been considered difficult and uninteresting, thus affecting the literacy skills of elementary school students. The research method used is classroom action research (PTK), which consists of two cycles. The data collection methods used were test sheets, observations, field notes and documentation. The research was conducted at Kedungprimpen State Elementary School, Bojonegoro, East Java, especially in class IV social studies subjects. The research results show that the increase in literacy skills is reflected in the completeness of the learning outcomes obtained, namely 50% classical completeness in the pre-cycle, 72.22% classical completeness in cycle I, and 100% classical completeness in cycle II. This result has achieved the previously determined classical completeness, namely a minimum of 80% classical completeness. The application of ASEAN OPPET (adventurous envelope) media can improve the literacy skills of class VI students at Kedungprimpen State Elementary School